Bird Assemblages and Vegetation Structre along Urbanization Gradient in Central Region, Ghana - Opoku, Bright (University of Cape Coast, 2018)
Ghana forest cover has decreased to less than 20% of the original continuous forest due to deforestation through urbanisation, agricultural intensification and infrastructure development. What are left are modified fragmented patches to serve as home for wild animals. This work focused on avian assemblages along an urban to forest gradient in southern Ghana to document how different species, species groups and feeding guilds respond to urbanization using point count method. Mean avian diversity and abundance increased with urbanization. There was variation in the vegetation structure along the gradient of urbanisation although theoretically vegetation structure tends to decrease with urbanisation as some vegetation parameters like flowering and fruiting plants were high in urban habitat. This resulted in nectarivore being the most abundant in the urban habitat while insectivore being the most abundant in the suburban habitat. The total abundance of species that make up the various feeding guild differed across the habitat types. Regarding the relationship between bird diversity, abundance and vegetation parameters; bird diversity and abundance were positively correlated to percentage ground cover and average tree height whiles they were negatively correlated to number of shrubs, number of small trees and number of flowering plants. There was no single species utilising a single habitat because different species utilised one or more component of the vegetation structure differently as seen from the (Canonical Correspondence Analysis) CCA plot. In conclusion, avian assemblages, the number of species that make up the various feeding guild and feeding guild density are not limited by urbanisation but are represented spatially and temporary across the habitat gradient.
xiii, 88p:, ill.
Keywords: Avian Assemblages; Exurban; Fragmentation; Forest; Suburban; Urban; Vegetation structure